THE SIGNIFICANCE OF THE NOS3 G894T (GLU298ASP, RS1799983) GENE IN CARDIOVASCULAR ADAPTATION IN ADOLESCENT FOOTBALL PLAYERS - A.A. Ruzieva (Journal of modern medicine, 2026)
In recent years, among the genes associated with success in sports and adaptation to physical exertion, NOS3 (endothelial nitric oxide synthase gene) has garnered particular attention. Polymorphisms of the NOS3 gene affect nitric oxide synthesis, which in turn determines the state of endothelial function, vascular dilation, and hemodynamic adaptation processes. Objective. To evaluate the relationship between cardiovascular system adaptation indicators and NOS3 G894T (Glu298Asp, rs1799983) gene polymorphisms in adolescent football players. Research materials. The study included 100 adolescent football players who train regularly (AF group) and 60 adolescents who participate in sports as part of their school's physical education curriculum (SC group). Conclusion. In the study of the NOS3-G894T (rs1799983) polymorphism, the most favorable adaptation profile was observed in carriers of the GG genotype. They exhibited a lower resting heart rate, a higher incidence of physiological bradycardia, better parameters of autonomic heart rhythm regulation, more pronounced physiological myocardial remodeling, and optimal diastolic function values. Conversely, the presence of the T allele was associated with a decrease in the functional reserves of the cardiovascular system, a reduction in vagal nerve influence, and a shift in the autonomic balance towards sympathetic activity.